On the calculation of the righting lever curve for a damaged ship. (1st February 2018) - Ruponen, Pekka; Manderbacka, Teemu; Lindroth, Daniel
Abstract: The current damage stability criteria for ships are mainly based on the characteristics of the righting lever curve. The related calculations for different intermediate stages during the flooding process, and for the final equilibrium condition, are generally considered trivial. However, with the increased computing capacity the regulations are developing towards a more realistic assessment of the intermediate stages of flooding. Most notably, time-domain flooding simulation has become a viable option. Consequently, the practices and assumptions related to the calculation of the righting lever curve for a damaged ship need to be addressed. This paper presents these challenges from different perspectives, and reviews available numerical methods for assessment of damage stability. Sample calculation results with different methods are presented for various damage scenarios, and the results are thoroughly analyzed and discussed. Finally, some recommendations on using the different methods are given. Highlights: Different methods for calculation of the GZ curve for a damaged ship are reviewed. The effect of time-dependency on the GZ curve for a flooding ship is discussed. Calculation examples for different damage cases are presented. Structures in flooded compartments can restrict free flow of water from/to sea.